Community Participation Model And The Role Of Local Wisdom In The Prevention Of Corruption Of Village Funds - Eko Handoyo Eko Handoyo; Wahyu Beny Mukti Setiyawan Wahyu Beny Mukti Setiyawan; Natal Kristiono Natal Kristiono; Siti Muslikhatul Ummah Siti Muslikhatul Ummah; Muhammad Wildan Khunaefi Muhammad Wildan Khunaefi; Fathurrahman Prasetyo Aji Fathurrahman Prasetyo Aji (Journal Of Social Science (JoSS), 2023)
The study of anti-corruption literature may not be new, however, most anti-corruption literature studies in Indonesia focus on anti-corruption education. Meanwhile, when discussing anti-corruption villages, religion is often used as a method of anti-corruption hand-cutting. Unlike these studies, this study will focus on finding models of community participation and the role of local wisdom with Max Weber's social action theory and Mayer N. Zald-John D. Mc Carthy's resource mobilization theory as its analysis knife. Using qualitative research methods and Participatory Rural Appraisal (PRA) approach this study, finally found that "Taqdim political-economic empowerment based on traditional ethics and religion" is a model of community participation that includes the local wisdom of Sentang village. This model then also carried out five resource mobilizations to achieve corruption prevention of village funds. The realization of this model can then be grouped into types of social action consisting of actions based on goals, values, affections, and traditions. Based on the conclusion of the thesis, this study has succeeded in finding a model of community participation and the role of local wisdom in preventing corruption of village funds. Thus, this study has provided new insights into preventing corruption of village funds through the integration of participation models and the role of local wisdom. In practical terms, this insight can automatically be used as a consideration for policymakers in determining the prevention of corruption in village funds.